”It’s not about the tech but the mindset”: Sociotechnical Imaginaries of the Future Data Driven Classroom in Sweden and Estonia (Sociologisk Forskning, 2025)
This study discusses how representatives of the EdTech sector and stakeholders within the field of educational policy in Sweden and Estonia imagine the classroom of the future and the role of digital technologies in these visions. Based on material from a series of future workshops where a total of nine groups gathered to discuss future school development, the study analyzes the sociotechnical imaginaries of education present in each country and the logics underpinning the datafication of the education sector. The results show that participants in both countries highlight datafication as a means to achieve a more individualized educational system, but they also identify tensions between this vision and another common imaginary of a school with diverse learning environments and teaching methods. The study also discusses national differences in the material and how they reflect the educational politics in each country where Estonia uses digitalization to strengthen its national identity as a modern and innovative tech nation, whereas in Sweden there is a growing tendency to question the effects of digital technologies on students’ well-being and cognitive development. These findings contribute to critical research on the datafication of schooling by offering a deeper understanding of the relation between national and global imaginaries of educational futures.
Keywords: datafication; education; future workshops; educational technologies; sociotechnical imaginaries